Light and ventilation in city schools - Smith, Ernest P. (My University, 1895)
Introduction: It may be a commonplace expression but it is a profound truth that we are living today in the midst of revolutions. The opening up of new fields of scientific truths, leading in their application to thousands of new inventions and improvements in methods, forces us to analyze and readjust our industrial life and our educational ideas. Education never leads in the development of such readjustments; sometimes it is even a century behind, but today it is following closely the newest and the best and is working out great changes…Society will demand then, and the demand will be granted, that more favorable conditions shall surround the boys and girls at school. They will have the glow of health and contentment upon their faces instead of the sallow, sullen, careworn expression that now characterizes the average child in public city schools, confined to a place little better than a dungeon and a much worse place, more injurious to the health than the criminal is given in the penitentiaries. Expense should be but an incidental consideration when discussing the construction of school buildings and the apparatus for securing favorable sanitary requirements. Too frequently cost is the only consideration taken into account. Such evils cannot long prevail if the public learn the dangers resulting from them. They will be aroused to that activity so much needed and a reform will soon be the result.
Citation: Smith, Ernest P. Light and ventilation in city schools. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Light; Ventilation; Schools; Theses; Manuscripts (documents)